Applying GIS for Vulnerability Assessment of Coastal Ecosystems in Hai Phong City - Canh, Pham Xuan; Thach, Nguyen Ngoc; Hieu, Nguyen; Phuong, Doan Thu; Hang, Bui Thu (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Economic developments in coastal zone in Hai Phong city such as industrial zones, seaports have significant impacts on living space and environment of ecosystems. Especially in climate change theme as the rising of average temperature and global mean sea level, the ecosystems here are at high risk of vulnerability. Vulnerability assesment of ecosystems is very important to detect the risk of future ecosystem degradation, which helps to define the timely measures to preserve and restore them. Based on the study of natural and socio-economic conditions affecting the environment of ecosystem, the research developed indicators to evaluate the vulnerability of ecosystems which are divided into three groups: sensitivity, exposure, and adaptive capacity. These indicators after normalization are the inputs for mapping vulnerability assessment of ecosystems through GIS tools. The vulnerability are divided into five levels: very low, low, medium, high and very high. Keywords Vulnerability, sensitivity, exposure, adaptive capacity, coastal ecosystem References [1] Bộ Tài nguyên & Môi trường – Viện khoa học khí tượng thủy văn và Môi Trường (2012), Kịch bản biến đổi khí hậu, nước biển dâng cho Việt Nam. [2] Nguyễn Hiệu (2002), Nghiên cứu biến động địa hình khu vực cửa sông Ba Lạt và lân cận phục vụ quản lý đới bờ, Luận văn thạc sĩ khoa học mã 01 07 03. [3] Nguyễn Thị Thúy Nga, Bùi Thị Hằng, Phạm Công Sơn Hải (2016), “Nghiên cứu xác lập sự phân bố không gian các hệ sinh thái ở đới bờ biển thành phố Hải Phòng trên cơ sở ứng dụng viễn thám và hệ thông tin địa lý (GIS)”, Báo cáo khoa học sinh viên khoa Địa lý - ĐH Khoa học tự nhiên năm 2016. [4] Vũ Văn Phái (2006), Cơ sở địa lý tự nhiên biển và đại dương, NXB Đại học quốc gia Hà Nội Hà Nội. [5] WWF (2013), Đánh giá tính dễ tổn thương trước biến đổi khí hậu của các hệ sinh thái tại Việt Nam. Tiếng anh [6] Alexander D. (1991), "Natural disasters", A framework for research and teaching disaster, 15(3), p 209-226 [7] Cutter, S. L., J. T. Mitchell and M. S. Scott (2000). "Revealing the vulnerability of people and places: a case study of Georgetown County, South Carolina." Annals of the Association of American Geographers 90(4): 713-737. [8] Downing, TE, Butterfield, R, Cohen, S, Huq, S, Moss, R, Rahman, A, Sokona, Y and Stephen (2001), "Vulnerability Indices: Climate Change Impacts and Adaptation", UNEP Policy Series, UNEP, Nairobi. [9] Fekete A. (2009), "Assessment of Social Vulnerability for River-Floods in Germany", Inaugural-Dissertation zur Erlangung des Grades DoktorIngenieur (Dr. -Ing.) der Hohen Landwirtschaftlichen Fakultät der Rheinischen FriedrichsWilhelm-Universität zu Bonn. 2009 [10] Gabor, T. and T.K.Griffith (1979), The assessment of community vulnerability to acute hazardous materials incidents. Unpublished paper for emergency planning research conference, arnprior?, Ontario, June 29-31, 1979 [11] IPCC (2001) Climate change 2001: impacts, adaptations and vulnerability. Contribution of Working Group II to the Third Assesment Report of the Intergovernmental Panel on Climate Change (IPCC). Cambridge University Press, Cambridge. [12] Joanne Linnerooth-Bayer (2010), "Risk and Vulnerability Program". Research Plan 2006-2010”. [13] Laura Tremblay-Boyer and Eric Ross Anderson, PANAMA [14] Quantitative assessment of Vulnerability to Climate Change (Computation of Vulnerability Indices) [15] Timmerman, P. 1981, Vulnerability, Resilience and the collapse of the society, Environmental monograph 1, Toronto: Institute of Environmental Studies, University of Toronto. [16] UNDRO (1982), Natural disasters and vulnerability analysis, Geneva: Office of the United Nations Disaster Relief Cocoordinator. [17] Watts M.J. and Bohle H.G. (1993), "The space of vulnerability: the causal structure of hunger and famine", Progress in Human Geography 17, p.43-67. [18] World Food Programme (WFP) 1999, Vulnerability Analysis and Mapping (VAM).